2007
DOI: 10.1002/cncr.22549
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of hepatitis B virus infection in B‐cell subtype non‐Hodgkin lymphoma compared with other cancers

Abstract: BACKGROUND.The authors investigated the prevalence of hepatitis B virus (HBV) infection by using serologic markers in non‐Hodgkin lymphoma (NHL) compared with other types of cancers in Chinese patients.METHODS.In this case‐control study, HBV and other hepatitis markers were compared between a study group and a control group. The study group included 587 patients with NHL (age range, 16–86 years), and the control group included 1237 patients (age range, 16–89 years) who were diagnosed with other cancers except … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
111
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 49 publications
13
111
4
1
Order By: Relevance
“…Recent reports examining HBV-DNA in serum have shown that occult HBV infection further adds to the associations of HBsAgpositive HBV infection with NHL and chronic lymphocytic leukemia. [30][31][32] It is also possible that some persons can be positive for HBV-DNA in hepatocytes or lymphocytes or both but negative in serum, which would further affect the association between HBV infection and NHL. …”
mentioning
confidence: 99%
“…Recent reports examining HBV-DNA in serum have shown that occult HBV infection further adds to the associations of HBsAgpositive HBV infection with NHL and chronic lymphocytic leukemia. [30][31][32] It is also possible that some persons can be positive for HBV-DNA in hepatocytes or lymphocytes or both but negative in serum, which would further affect the association between HBV infection and NHL. …”
mentioning
confidence: 99%
“…This has, in part, been ascribed to different rates of hepatitis infections in the general population of the respective countries. Wang reported a decreased rate of HBV infections in patients with T-cell lymphoma compared to patients with B-cell malignancies [28].…”
Section: Discussionmentioning
confidence: 99%
“…7 It was reported that HBV plays a role in the development of B-cell NHL. 8 In contrast, primary gastric lymphoma with a T-cell phenotype is relatively rare, accounting for only 7% of primary gastric lymphomas in HTLV-1 infected endemic areas and a relatively large number of such cases are secondary gastric involvement of adult T-cell leukemia. Primary gastric T-cell lymphoma without HTLV-1 infection is rare, and sporadic cases have been reported.…”
Section: Epidemologymentioning
confidence: 99%